Influences of the wall thickness on the granular dispersion in a dense gas–solid coaxial jet. (May 2016) - Fang, Chenchen; Xu, Jianliang; Zhao, Hui; Li, Weifeng; Liu, Haifeng
Highlights: The wave dispersion fades away with the increase of the wall thickness. The wavelength increases linearly with the modified vorticity thickness. The relation of the amplitude is feasible for the wave dispersion. The granular dispersion angle is proportional to the annular gas velocity. Abstract: The granular dispersion for different wall thicknesses of the inner channel in a dense gas–solid coaxial jet is investigated by morphology. In the wave dispersion, the Kelvin–Helmholtz instability has a strong influence on the granular stream. However, increasing the wall thickness damps the K–H instability, namely weakens the wave dispersion. Consequently, the non-dimensional wavelength increases and the non-dimensional amplitude decreases as the wall thickness increases for the same annular gas velocity. The instability analysis combining with the modification of the vorticity thickness of the annular gas stream indicates that the non-dimensional wavelength increases linearly with the non-dimensional modified vorticity thickness. The relation between the amplitude of the granular dispersion and the non-dimensional modified vorticity thickness is reliable for the wave dispersion as well. In addition, the granular dispersion angle is proportional to the annular gas velocity, which slightly depends on the wall thickness.